Clinical Impact of Thrombus Aspiration and Interaction With D-Dimer Levels in Patients With ST-Segment Elevation Myocardial Infarction Undergoing Primary Percutaneous Coronary Intervention - Li, Jun-feng; Lin, Zhi-wei; Chen, Chang-xi; Liang, Shi-qi; Du, Lei-lei; Qu, Xiang; Gao, Zhan; Huang, Yu-heng; Kong, Shu-ting; Chen, Jin-xin; Sun, Ling-yue; Zhou, Hao (Frontiers in Cardiovascular Medicine, 2021)
Objectives: To evaluate the effect of thrombus aspiration (TA) strategy on the outcomes and its interaction with D-dimer levels in patients with ST-segment elevation myocardial infarction (STEMI) during primary percutaneous coronary intervention (PCI) in “real-world” settings. Materials and Methods: This study included 1295 patients with STEMI who had undergone primary PCI with or without TA between January 2013 and June 2017. Patients were first divided into a TA+PCI group and a PCI-only group, baseline characteristics and long-term mortality between the two groups were analyzed. Furthermore, we studied the effect of TA on clinical outcomes of patients grouped according to quartiles of respective D-dimer levels. The primary outcome was all-cause mortality, and the secondary outcomes were new-onset heart failure (HF), rehospitalization, re-PCI, and stroke. Results: In original cohort, there were no significant differences in all-cause mortality between the TA+PCI and PCI-only groups (hazard ratio, 0.789; 95% confidence interval, 0.556–1.120; P=0.185). After a mean follow-up of 2.5 years, the all-cause mortality rates of patients in TA+PCI and PCI-only groups were 8.5% and 16.2%, respectively. Additionally, differences between two groups in terms of the risk of HF, re-PCI, re-hospitalization, and stroke were nonsignificant. However, after dividing into quartiles, as D-dimer levels increased, the all-cause mortality rate in the PCI group gradually increased (4.3% vs. 6.0% vs. 7.0% vs. 14.7%, P<0.001), while the death rate in the TA+PCI group did not significantly differ (4.6% vs. 5.0% vs. 4.0% vs. 3.75%, P=0.85). Besides, in quartile 3 and quartile 4 groups, the PCI-only group was associated with a higher risk of all-cause mortality than that of the TA+PCI group (Q3: 4.0% vs. 7.0%, P=0.029; Q4: 3.75% vs. 14.7%, P<0.001). Moreover, the multivariate logistic regression analysis demonstrated that TA is inversely associated with the primary outcome in the Q4 group (OR, 0.395; 95% CI, 0.164–0.949; P=0.038). Conclusions: The findings of our real-world study express that routine TA during PCI in STEMI did not improve clinical outcomes overall. However, patients in STEMI with a higher concentration of D-dimer might benefit from the use of TA during primary PCI. Large-scale studies are recommended to confirm the efficacy of TA.